Cytokine and Chemokine Profile in Individuals with Different Degrees of Periportal Fibrosis due to Schistosoma mansoni Infection - Robson Da Paixão De Souza; Luciana Santos Cardoso; Giuseppe Tittoni Varela Lopes; Maria Cecília F. Almeida; Ricardo Riccio Oliveira; Leda Maria Alcântara; Edgar M. Carvalho; Maria Ilma Araujo (Journal of Parasitology Research)
Periportal fibrosis in schistosomiasis has been associated to the host immune response to parasite antigens. We evaluated the immune response in S. mansoni infected individuals with different degrees of periportal fibrosis. Cytokine and chemokines were measured in serum and in supernatants of PBMC cultures stimulated with the soluble adult worm (SWAP) or egg (SEA) antigens, using a sandwich ELISA. The levels of IL-5 in response to SEA were higher in individuals with moderate to severe fibrosis (310.9 pg/mL) compared to individuals without fibrosis (36.8 pg/mL; P=0.0418). There was also a higher production of TNF-α in cultures stimulated with SWAP in patients with insipient fibrosis (1446 pg/mL) compared to those without fibrosis (756.1 pg/mL; P=0.0319). The serum levels of IL-13 and MIP-1α were higher in subjects without fibrosis than in those with moderate to severe fibrosis. However a positive association between serum levels of IL-13, TNF-α, MIP-1α, and RANTES and S. mansoni parasite burden was found. From these data we conclude that IL-5 and TNF-α may participate in liver pathology in schistosomiasis. The positive association between IL-13, TNF-α, MIP-1α, and RANTES with parasite burden, however, might predict the development of liver pathology.